2015
DOI: 10.1111/pace.12586
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction for Adverse Events during Initiation of Sotalol and Dofetilide for the Treatment of Atrial Fibrillation

Abstract: In conclusion, AEs are common during DF and SL initiation but rarely severe in hospitalized inpatients. Baseline QTc predicts AEs for DF patients only and AE are common even in "low-risk" patients. These results support in-hospital drug initiation for all DF and SL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Agusala and colleagues were not able to identify any significant predictors of ADRs. The authors concluded ADRs are common during initiation and that these results establish need for close inpatient monitoring [11] .The rates of bradycardia and QT prolongation during admission in our study of renally impaired patients (15.9% and 23.1%, respectively) are lower than that reported despite twice daily dosing strategy. Furthermore, sotalol product labeling describes bradycardia incidence of 13.1% [3] .…”
Section: Original Researchcontrasting
confidence: 47%
“…Agusala and colleagues were not able to identify any significant predictors of ADRs. The authors concluded ADRs are common during initiation and that these results establish need for close inpatient monitoring [11] .The rates of bradycardia and QT prolongation during admission in our study of renally impaired patients (15.9% and 23.1%, respectively) are lower than that reported despite twice daily dosing strategy. Furthermore, sotalol product labeling describes bradycardia incidence of 13.1% [3] .…”
Section: Original Researchcontrasting
confidence: 47%
“…Geographically, 12/36 studies were done in USA, multicenter studies account for 11/36 studies, one study was done in UK/France/Germany/Turkey/Greece/Taiwan/Iran, two studies were done in Switzerland. Study design distributions were: cross sectional studies in 3/36, prospective observational in 3/36, retrospective studies in 10/36 and randomized controlled trials in 19/36 ( Table 1 , [ 3 - 38 ]).…”
Section: Resultsmentioning
confidence: 99%
“…TdP was found in 49 patients (0.33 %), SCD was found in five patients and 586 were found to have all-cause mortality. Only two studies reported ventricular arrhythmias [ 3 , 36 ]; two studies reported TdP [ 9 , 19 ]; one study reported SCD [ 9 ]; and four studies reported death [ 18 - 20 , 36 ]. Remaining studies either didn’t report ventricular arrhythmias or didn’t have any episodes of ventricular arrhythmias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates are somewhat higher compared to those of similar single-center studies. 16,17 The mean maximal QTc interval during medication initiation was also higher in the nonstandard group. Additionally, it was greater than the maximum recommended QTc interval of 500 ms.…”
Section: Discussionmentioning
confidence: 90%